Poor images and the ostentation of the pixel: Relations between cinema and the internet in Videophilia (and other viral syndromes) - Ishii, Regiane Akemi (2020)
This article aims at conducting a film analysis of Videophilia (and Other Viral Syndromes) (2015), by Juan Daniel F. Molero, and its narrative and esthetic relationship with the Internet, highlighting the presence of glitches and datamoshing, techniques that increase the visibility of pixels. We will relate such use with the concept of poor images, a term coined by Hito Steyerl, in which the author presents the ambivalence of images that lose resolution to gain speed and diffusion. Recent reflections on film theory will also be mobilized through authors such as D. N. Rodowick, Francesco Casetti and Thomas Elsaesser. Thus, it will be possible to examine some of the ways with which cinema has confronted, acted on and responded to the status of contemporary images, where production and circulation become indistinguishable.